Children's Psychological Affect on Their Daily Life in Private Welfare Institutions - Cheong, Chong Chan; Sayuti, Rusimah; Abdul Hamid, Ahmad Shukri (UUM Press, 2020)
Children who are separated from their biological families have an unusual life experience compared to their counterparts residing with their biological families. This paper describes children's psychological affect by measuring their self-expression based on their daily experiences in welfare institutions. A total of 163 children in four private children's homes completed the Malay version of the Scale of Positive and Negative Experience (SPANE) developed by Ed Diener and Robert Biswas-Diener (2009). The results show that more than half of the children (60.1%) had high levels of positive expression, while 63.2 percent recorded intermediate levels of negative expression. In total, only 30.1 percent of the children had high affect balance. Independent sample t-test shows that male children had significant positive expression and higher affect balance compared to their female counterparts. Female children had higher negative expression than male children. Correlation analyses show that no significant relationships can be established between self-expression and the factors of age and length of stay at the private welfare institutions. Analysis of Covariance (ANCOVA) indicates that there was a significant difference in mean affect balance between male and female children while adjusting age and length of stay. This implies that gender is an important factor in the positive expression of children in out-of-home care. Any efforts to help the children feel positive about their living experience should begin by considering their gender.